خليّــة الاتصال فــي مواجهة رهــانات أزمــة فيضانـات غردايـة 2008 - بوهلي, فطيمة (جامعة الوادي - University of Eloued, 2015)
يَعتمد الاتصال طرائق وأساليب عدّة في نقل المعلومات في الحياة اليومية للفرد والجماعة والتي تسمح بمواجهة وتسيير المخاطر والحوادث الطارئة، ما جعل بالمختصّين في علم الإدارة يُولون اهتمامًا كبيرًا بالاتصال ويُشكّلون رؤى واسعة حول كيفية استغلاله وإدارته، حيث ظنّ بعض الباحثين في ستينيات القرن العشرين بأهمية دور الإذاعة في تنبيه الجمهور بأضرار الكوارث المحتَمَلِ وُقُوعِها، ومعها تطورت البحوث لتفرض حيزًا مهمًا لإدارة الأزمات في كافة مناحي الحياة ومؤسساتها، فإذا كان للاتصال دورًا بارزًا في الحياة اليومية للإنسان فإنّه اليوم أكثر أهمّية في حالات الأزمات والكوارث وبخاصة تلك الناجمة عن المخاطر الطبيعية أو التكنولوجية، حيث تشهد البشرية أكثر مما سبق تطورات اقتصـادية وصناعية واجتماعية وسياسية تسبّبت إلـــى جانب التغيرات المناخية والبيئية في اصطدام العالم من حين لآخر بكوارث وأزمات عدّة، نذكر منها على ســبيل المثال الأزمة المالية العالمية (2008)، والأزمة الغذائية وكوارث إعصار كاترينا بالولايات المتّحدة الأمريكية، إعصار تسونامي بآسيا الجنوبية، زلزال أكتوبر (2005) بباكستان، فيضانات (10/11/ 2001) بباب .. Abstract: Contact depends several methods and techniques in the transfer of information in the daily life of the individual and the group, which allow face and running the risk of accidents and emergency. What makes the specialists in the science of management attach great importance to communication and make up visions and wide about how to exploit and management, Because of that Some researchers thought in the sixties of the twentieth century the importance of the role of radio in the damaged alert the public of possible disasters, along with the research evolved to impose an important aspect of crisis management in all walks of life and its institutions. So if the connection is a prominent role in everyday human life, it is today more important in crisis situations and disasters, particularly those caused by natural hazards or technological, in terms of human experience more than ever before, economic and industrial developments, social and political triggered along with climatic and environmental changes in the collision of the world from time to time disasters the crises are several, among them - for instance, the global financial crisis (2008), the food crisis and the disaster of Hurricane Katrina in the United States, the tsunami and South Asia, October earthquake (2005), Pakistan, floods (10.11.2001) Bab el wad in Algiers
مقال
Keywords: اتصال الأزمات – خلية الأزمة – السيناريو الاتصالي; Crisis Communication - The Crisis Cell Communication - Communication Scenario